Hammer throw: Legs or arms? - Strelnitzki, V.; Sedykh, Y. (Track Coach, 2018)
Contrary to widespread opinion, in advanced hammer throwing technique the arms are not a passive continuation of the hammer's wire but rather an active driver of the hammer. Braced to form a rigid "triangle," preventing sideways movements relative to the torso, the arms increase the radius of the "drive circle," which increases the tangential force accelerating the hammer along its orbit.